2018
DOI: 10.1111/dom.13395
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of biguanide transporters in human fat cells and their impact on lipolysis

Abstract: While human fat cells primarily express three biguanide transporters, our data suggest that PMAT is the primary target for development of fat cell-specific antilipolytic biguanides with high sensitivity and potency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The activation of AMPK reduces cell proliferation through negatively regulates mTOR signaling (43). Recent results showed that NT-1044 exhibited higher AMPK activation than metformin at the same dosage in differentiated human adipocytes (44).In its role as an AMPK activator, the anti-tumorigenic activity of NT-1044 appears similar to that of metformin, which has been shown to significantly decrease proliferation of several human cancer cell lines in vitro, including endometrial cancer (25,26,(45)(46)(47). Since AMPK negatively controls mTOR activation and mTOR is a downstream effector of AKT, Activation of AMPK is considered to be a possible therapeutic target for cancers that contain high AKT activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of AMPK reduces cell proliferation through negatively regulates mTOR signaling (43). Recent results showed that NT-1044 exhibited higher AMPK activation than metformin at the same dosage in differentiated human adipocytes (44).In its role as an AMPK activator, the anti-tumorigenic activity of NT-1044 appears similar to that of metformin, which has been shown to significantly decrease proliferation of several human cancer cell lines in vitro, including endometrial cancer (25,26,(45)(46)(47). Since AMPK negatively controls mTOR activation and mTOR is a downstream effector of AKT, Activation of AMPK is considered to be a possible therapeutic target for cancers that contain high AKT activity (48).…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of isoprenaline-stimulated lipolysis in si NUP85 -transfected hASCs was performed as described previously 19 . In brief, cells were incubated for 3 h in DMEM/F12 medium supplemented with 20 mg/ml of BSA and with or without isoprenaline (1 µmol/l).…”
Section: Methodsmentioning
confidence: 99%
“…This figure is a graphical representation of the data assimilated by Prof. Hermann Koepsell in Table 6 of his 2020 review, Organic Cation Transporters in Health and Disease 9 for OCT1, OCT2, OCT3, MATE1, and MATE2-K, based on >130 references therein; plus data reported for PMAT expression by numerous research labs. 5,[10][11][12][13][14] The vast majority of these distribution data is based upon mRNA expression reports, not protein expression. Tissues reported include adipose tissue, adrenal glands, bladder, bone marrow, brain and neurovasculature, eye, heart, intestines, kidney, liver, lungs/trachea, salivary glands, skeletal muscle, skin, spleen, stomach, thymus and thyroid.…”
Section: Pharmacological Findingsmentioning
confidence: 99%
“… Distribution of uptake 2 transporters in major organs and tissues throughout the body . This figure is a graphical representation of the data assimilated by Prof. Hermann Koepsell in Table 6 of his 2020 review, Organic Cation Transporters in Health and Disease 9 for OCT1, OCT2, OCT3, MATE1, and MATE2‐K, based on >130 references therein; plus data reported for PMAT expression by numerous research labs 5,10–14 . The vast majority of these distribution data is based upon mRNA expression reports, not protein expression.…”
Section: Introductionmentioning
confidence: 99%